Structure, Spectral Features, Bioactivity and Light Harvesting Properties of Methyl and Dimethyl Anthracene: Experimental and First Principle Studies. (21st October 2021) - Rao, D. Jagadeeswara; Mary, Y. Sheena; Mary, Y. Shyma; Resmi, K. S.; Thomas, Renjith
Abstract: The quantum chemical calculation of 9-methylanthracene and 2, 3-dimethylanthracene molecules were carried out (9MA and 23DMA). The Density Functional Theory (DFT) by the method RB3LYP with the basis set of 6-311 + G(d) were performed. The Fourier Transform Infra Red (FTIR) spectrum and FT-Raman spectrum of the compounds were recorded in the region 4000–400 cm −1 and 4000–50 cm −1, respectively. The theoretical frequencies were scaled down and compared with experimental FT-IR and FT-Raman spectral values and they agree well. The Natural Bond analysis is performed to gauge the Lewis structure of the molecule. The first order hyperpolarizability values were calculated from the Non-Linear Optical (NLO) studies of the title molecules and compared with standard reference value of Urea. The molecular electrostatic potential surface is obtained and used to get the nucleophilic and electrophilic sites. The molecular docking study for title compound indicates anti cancer properties. Molecules show excellent Light Harvesting Efficiency, hence can be used in DSSC's.